2013
DOI: 10.1371/journal.pone.0080639
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness Analysis of the Bivalent and Quadrivalent Human Papillomavirus Vaccines from a Societal Perspective in Colombia

Abstract: ObjectiveTo compare costs and effectiveness of three strategies used against cervical cancer (CC) and genital warts: (i) Screening for CC; (ii) Bivalent Human Papillomavirus (HPV) 16/18 vaccine added to screening; (iii) Quadrivalent HPV 6/11/16/18 vaccine added to screening. MethodsA Markov model was designed in order to simulate the natural history of the disease from 12 years of age (vaccination) until death. Transition probabilities were selected or adjusted to match the HPV infection profile in Colombia. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 39 publications
2
13
0
6
Order By: Relevance
“…These results were in line with the results from previous studies in other countries, which confirmed that the ICER of HPV vaccination has been considered to be sensitive to vaccine price [68,69] and discount rate [70][71][72]. Regarding duration of protection, since most of the long-term effectiveness of the vaccine has not been obtained yet, the authors were forced to use assumptions and/or intermediate outcomes for their model.…”
Section: Discussion and Limitationsupporting
confidence: 83%
“…These results were in line with the results from previous studies in other countries, which confirmed that the ICER of HPV vaccination has been considered to be sensitive to vaccine price [68,69] and discount rate [70][71][72]. Regarding duration of protection, since most of the long-term effectiveness of the vaccine has not been obtained yet, the authors were forced to use assumptions and/or intermediate outcomes for their model.…”
Section: Discussion and Limitationsupporting
confidence: 83%
“…Of course, some studies about HPV vaccination of targeted groups have demonstrated economic value (Aponte-Gonzalez et al, 2013;Demarteau et al, 2013;Drolet et al, 2013;Elbasha et al, 2009;English et al, 2013;Fesenfeld et al, 2013;Kim et al, 2007;Natunen et al, 2013;Turner et al, 2013;Woertman and van der Wilt, 2013). However, the present study also considered the home environment when defining the socially vulnerable group.…”
Section: Discussionmentioning
confidence: 88%
“…Se ha reportado también que la vacunación de mujeres tendría un impacto beneficioso en varones debido a la protección comunitaria (25) . En relación al tipo de vacuna a emplear, diversos estudios han reportado que la vacuna cuadrivalente es más costo-efectiva que la vacuna bivalente (25,27,40) , principalmente debido al efecto a corto plazo sobre las VAG. Debemos resaltar el estudio de Jit et al, en el cual reportan que si bien la vacuna cuadrivalente es más costo-efectiva, las diferencias con la vacuna bivalente serían muy marginales, similar a lo reportado por nosotros (40) .…”
Section: Discussionunclassified
“…Existen estudios en otras realidades que han reportado que la vacunación de niñas no infectadas contra el VPH es costo-efectiva (25)(26)(27) . Sin embargo, no es posible extrapolar los resultados al Perú, ya que dichos estudios se basan en costos y frecuencias de las patologías y sus complicaciones a nivel local.…”
Section: Introductionunclassified